Optical steganography transmission of optical CDMA signals over a public BPSK channel. Issue 6 (1st August 2016) - Yen, Chih-Ta; Huang, Guan-Jie
Abstract : Purpose: – The purpose of this paper is to propose a new optical steganography framework that can be applied to public optical binary phase-shift keying (BPSK) systems by transmitting a stealth spectrum-amplitude-coded optical code-division multiple-access signal through a BPSK link. Design/methodology/approach: – By using high-dispersion elements, the stealth data pulses temporally stretch and the amplitude of the signal decreases after stretching. Thus, the signal can be hidden underneath the public signal and system noise. At the receiver end, a polarizer is used for removing the public BPSK signal and the stealth signal is successfully recovered by a balanced detector. Findings: – In a simulation, the bit-error rate (BER) performance improved when the stealth power increased. Research limitations/implications: – The BER performance worsens when the noise power become large. Future work will consider increasing the system performance during high-noise power situation. Practical implications: – By properly adjusting the power of the amplified spontaneous emission noise, the stealth signal can be hidden well in the public channel while producing minimal influence on the public BPSK signal. Originality/value: – In conclusion, the proposed optical steganography framework makes it more difficult for eavesdroppers to detect and intercept the hidden stealth channel under public transmission, even when using a dispersion compensation scheme.